2021
DOI: 10.15252/embj.2021107766
|View full text |Cite
|
Sign up to set email alerts
|

GRASP55 regulates intra‐Golgi localization of glycosylation enzymes to control glycosphingolipid biosynthesis

Abstract: The Golgi apparatus, the main glycosylation station of the cell, consists of a stack of discontinuous cisternae. Glycosylation enzymes are usually concentrated in one or two specific cisternae along the cis‐trans axis of the organelle. How such compartmentalized localization of enzymes is achieved and how it contributes to glycosylation are not clear. Here, we show that the Golgi matrix protein GRASP55 directs the compartmentalized localization of key enzymes involved in glycosphingolipid (GSL) biosynthesis. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 73 publications
1
28
2
Order By: Relevance
“…Golgi-resident proteins were also depleted in COPI vesicles visible in S. cerevisiae [ 23 ]. These data appear to contradict data published by Martinez-Menarguez et al [ 52 ], Gilchrist et al [ 51 ], Rizzo et al [ 53 ], and Pothukuchi et al [ 54 ]. We analysed these data in detail and demonstrated that they could also be interpreted from the point of view of the CMPM ([ 38 ], see below).…”
Section: Discussioncontrasting
confidence: 75%
“…Golgi-resident proteins were also depleted in COPI vesicles visible in S. cerevisiae [ 23 ]. These data appear to contradict data published by Martinez-Menarguez et al [ 52 ], Gilchrist et al [ 51 ], Rizzo et al [ 53 ], and Pothukuchi et al [ 54 ]. We analysed these data in detail and demonstrated that they could also be interpreted from the point of view of the CMPM ([ 38 ], see below).…”
Section: Discussioncontrasting
confidence: 75%
“…Otherwise, Golgi matrix protein GRASP55 prevents the retrograde transport of glycosyltransferases, retaining these enzymes in the trans Golgi. Therefore, a balance between the actions of GOLPH3 and GRASP55 determines the localization and levels of intra-Golgi glycosyltransferases ( Pothukuchi et al, 2021 ).…”
Section: Gb3 Structure Synthesis and Degradationmentioning
confidence: 99%
“…GnT1IP-L can interact directly with GlcNAcT-I, causing its mislocalization from the medial-Golgi to the ER, ERGIC, and cis-Golgi [ 114 ]. Golgi-resident GRASP55 regulated the subcellular localization of glycosylation protein involved in glycosphingolipid biosynthesis by direct interaction [ 115 ]. The L95LGV98 sequence in the GRASP domain of GRASP55 interacted with the cytosolic tail of GlcCer synthase (GCS), which catalyzes the critical step in glycosphingolipid biosynthesis [ 115 ].…”
Section: Recycling Of Glycosyltransferase and Glycosidases Involved I...mentioning
confidence: 99%
“…Golgi-resident GRASP55 regulated the subcellular localization of glycosylation protein involved in glycosphingolipid biosynthesis by direct interaction [ 115 ]. The L95LGV98 sequence in the GRASP domain of GRASP55 interacted with the cytosolic tail of GlcCer synthase (GCS), which catalyzes the critical step in glycosphingolipid biosynthesis [ 115 ]. The direct binding with GRASP55 promoted the correct subcellular localization of GCS by preventing GCS from entering in the retrograde transportation [ 115 ].…”
Section: Recycling Of Glycosyltransferase and Glycosidases Involved I...mentioning
confidence: 99%
See 1 more Smart Citation